1992
DOI: 10.1104/pp.99.4.1294
|View full text |Cite
|
Sign up to set email alerts
|

Root Respiration Associated with Ammonium and Nitrate Absorption and Assimilation by Barley

Abstract: We examined nitrate assimilation and root gas fluxes in a wildtype barley (Hordeum vulgare L. cv Steptoe), a mutant (narla) deficient in NADH nitrate reductase, and a mutant (narla;nar7w) deficient in both NADH and NAD(P)H nitrate reductases. Estimates of in vivo nitrate assimilation from excised roots and whole plants indicated that the narla mutation influences assimilation only in the shoot and that exposure to N03-induced shoot nitrate reduction more slowly than root nitrate reduction in all three genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
234
1
15

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(260 citation statements)
references
References 27 publications
10
234
1
15
Order By: Relevance
“…A reação no processo de assimilação do amônio requer redutor biológico -NAD(P)H, ou ferrodoxina provenientes da fase fotoquímica e de transferência de elétrons (fluxo linear de elétrons a partir da água através do PSII e do PSI até os receptores) da fotossíntese (TAIZ;ZEIGER, 2008). Na raiz, o suprimento de redutor é via processo respiratório (BLOOM et al, 1992).…”
Section: Introductionunclassified
“…A reação no processo de assimilação do amônio requer redutor biológico -NAD(P)H, ou ferrodoxina provenientes da fase fotoquímica e de transferência de elétrons (fluxo linear de elétrons a partir da água através do PSII e do PSI até os receptores) da fotossíntese (TAIZ;ZEIGER, 2008). Na raiz, o suprimento de redutor é via processo respiratório (BLOOM et al, 1992).…”
Section: Introductionunclassified
“…These authors concluded that nitrate uptake was regulated by the flows of carbohydrates from the shoots to the roots. However, Bloom, Sukrapanna & Warner (1992) calculated that only 5% of root carbon catabolism was coupled to nitrate uptake. In the present investigations the plants were supplied very well with light in a 16 h photoperiod in precultivation compared with other greenhouse plants.…”
Section: Time Courses Of Net Nitrate Uptake Ratesmentioning
confidence: 99%
“…Subsequent steps in nitrate metabolism, nitrate reduction and ammonium assimilation, are also inducible and energy dependent since reducing power, ATP and C-skeletons are needed. The uptake and assimilation of ammonium and nitrate require a significant amount of root respiration (Bloom, Sukrapanna & Warner 1992). Hence in an intact plant, nitrate uptake, N metabolism, C metabolism and ultimately photosynthesis are all linked.…”
Section: Introductionmentioning
confidence: 99%
“…Root uptake and assimilation of NO $ and NH % are energy-requiring processes (Bloom et al, 1992 ;Lambers, 1996), and because elevated CO # can enhance the supply of root respiratory substrates (Tschaplinski et al, 1993 ;BassiriRad et al, 1996b), metabolically regulated processes such as root N uptake are expected to be stimulated under elevated CO # . However, recent studies of NO $ and NH % uptake in response to elevated atmospheric CO # have shown surprising and sometimes conflicting results.…”
Section: mentioning
confidence: 99%